1996
DOI: 10.1063/1.116856
|View full text |Cite
|
Sign up to set email alerts
|

Key trade-offs for second harmonic generation in poled polymers

Abstract: We discuss the critical trade-off between the spectral dispersion in the second order nonlinearity d(2) and the linear absorption coefficient for second harmonic generation (SHG) by the mixing of copropagating or counterpropagating fundamental beams in poled polymers. The 4-dimethylamino–4′-nitrostilbene side-chain polymer is used as a specific example. The predictive power of the classical two-level model for SHG is also assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 6 publications
2
38
0
Order By: Relevance
“…Previously published data 6 showed that the wavelength dispersion of the absorption in the side-chain polymer ͑SCP͒ DANS, measured either by thin-film transmission in the visible or waveguide loss in the near infrared, could fit well with a Voigt profile ͑in-homogeneously broadened absorption model͒ as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previously published data 6 showed that the wavelength dispersion of the absorption in the side-chain polymer ͑SCP͒ DANS, measured either by thin-film transmission in the visible or waveguide loss in the near infrared, could fit well with a Voigt profile ͑in-homogeneously broadened absorption model͒ as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 58%
“…DANS SCP 1 absorption spectrum derived from thin-film transmission in the visible and waveguide propagation losses in the infrared, fitted to a Voigt profile. 6 Note that in this representation the linear behavior of the near-infrared tail of the absorption is valid over a spectral range of several hundreds of nanometers and several orders of magnitude in absorption values. acceptor, 12-16 have a cyanogroup as a primary acceptor, and 17 and 18 have both nitroacceptor and cyanoacceptor groups.…”
mentioning
confidence: 96%
“…However, the loss near the SH wavelength of the pump signal is comparatively low, 3.9 dB/ cm, as predicted, due to the short cutoff wavelength. As a reference, a DANS (4-dimethylamino-4'-nitrostilbene) side-chain polymer with k max of 432 nm showed¨25 dB/cm of loss at this wavelength [4]. The refractive indexes of the NLO copolymer film for TE-and TM-polarized light are 1.5964 and 1.5944, respectively, at a wavelength of 1.55 Am.…”
Section: Resultsmentioning
confidence: 99%
“…Nonlinear optical (NLO) polymers have been actively developed as substitutes for the inorganic crystals because the properties of these polymers include high nonlinearity, easy waveguide fabrication, and flexible waveguide design. At the same time, an NLO polymer waveguide exhibits high optical losses at communication wavelengths because of the intrinsic material absorption caused by the vibration overtones of the polymer main chain and the chromophore [4] and because of the scattering loss caused by poling processes and waveguide fabrications [5]. No results on DFG from a polymeric waveguide have been reported due to these critical disadvantages.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, periodically poled polymer waveguides have resulted in low SH generation ͑SHG͒ efficiencies of 0.05% W −1 cm −2 . 8 An alternative QPM approach based on a segment structure has been implemented to overcome the indicated problems with QPM and has shown an early result 9 of 0.4% W −1 cm −2 .…”
mentioning
confidence: 99%